2018
DOI: 10.1002/chem.201802546
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Tetrasubstituted Olefins by Copper‐Mediated Acetoxythiolation of Internal Alkynes: Scope and Mechanistic Studies

Abstract: The Cu-mediated synthesis of tetrasubstituted olefins by the addition of an acetate group and a thiolate to an unactivated internal alkyne is described. The reaction is fully stereoselective, because only the E alkene is obtained. If the alkyne is asymmetric, the reaction also shows a very high degree of regioselectivity. The mechanism of the reaction is elucidated by DFT methods, which show that it takes place through Cu-stabilized radical species. Calculations highlight the crucial role of the dimeric copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 105 publications
(192 reference statements)
0
9
0
Order By: Relevance
“…Because of the existence of highly covalent Fe–S bonds in oxidized intermediate A , an unpaired electron can be delocalized over iron and sulfur atoms to generate iron-stabilized thiyl radicals B , which are responsible for ethylene addition to form new C–S bond to produce adduct 2a­[BPh 4 ] . Similarly, the generation of the metal-stabilized thiyl radical as a key intermediate for further C–S bond formation with alkenes or alkynes was also observed in mononuclear ruthenium , and copper systems . Interestingly, in the absence of ethylene, iron-stabilized thiyl radical will self-assemble into reported diiron complex with a tpdt bridge in moderate yield .…”
Section: Results and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Because of the existence of highly covalent Fe–S bonds in oxidized intermediate A , an unpaired electron can be delocalized over iron and sulfur atoms to generate iron-stabilized thiyl radicals B , which are responsible for ethylene addition to form new C–S bond to produce adduct 2a­[BPh 4 ] . Similarly, the generation of the metal-stabilized thiyl radical as a key intermediate for further C–S bond formation with alkenes or alkynes was also observed in mononuclear ruthenium , and copper systems . Interestingly, in the absence of ethylene, iron-stabilized thiyl radical will self-assemble into reported diiron complex with a tpdt bridge in moderate yield .…”
Section: Results and Discussionmentioning
confidence: 81%
“…Similarly, the generation of the metal-stabilized thiyl radical as a key intermediate for further C−S bond formation with alkenes or alkynes was also observed in mononuclear ruthenium 6,8a and copper systems. 32 Interestingly, in the absence of ethylene, iron-stabilized thiyl radical will self-assemble into reported diiron complex with a tpdt bridge in moderate yield. 15 This result is different from other metal complex systems involving thiyl radicals, such as those of Goh's 10 and Wieghardt's 33 work, which all involve the generation of a coordinated thiyl radical and then intermolecular coupling to give the corresponding disulfide complexes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Matsubara et al reported the synthesis of tetrasubstituted ( Z )-β-aminocarbonyl vinyl sulfides via nickel-catalyzed thiocarbamoylation of internal alkynes with thiocarbamates . Urriolabeitia and co-workers described a copper-mediated acetoxythiolation of internal alkynes with thiols under microwave conditions for the synthesis of tetrasubstituted ( E )-β-acetoxyalkenyl sulfides . However, these reported methods generally suffer from some drawbacks such as the limited substrate scope, moderate yields, and poor regio- or stereoselectivities.…”
Section: Introductionmentioning
confidence: 90%
“…Reagents such as sodium tert-butoxide and copper diacetate keep aggregated structures in non-polar solvent environments, and their description as monomeric species in QM calculations could be misleading. [16,17] The same issue arises with iodosylbenzene (PhIO) a polymeric solid of low solubility. [18] To build up a reliable energy profile, all the species that can influence the energy of the system in each step of a catalytic cycle should be taken into account.…”
Section: The Chemical Modelmentioning
confidence: 99%
“…Attention should also be paid to the speciation of simple reagents, which can be very solvent dependent. Reagents such as sodium tert ‐butoxide and copper diacetate keep aggregated structures in non‐polar solvent environments, and their description as monomeric species in QM calculations could be misleading [16,17] . The same issue arises with iodosylbenzene (PhIO) a polymeric solid of low solubility [18] …”
Section: The Chemical Modelmentioning
confidence: 99%